A Theological Response of the Chapel of the Light, the University of Ilorin, to the Covid19 Pandemic - Caleb Oladokun Ogunkunle (Pharos Journal of Theology, 2022)
The entire world was bedeviled with fear and anxiety as a result of Covid 19 pandemic that has ravaged the world. The pandemic affected every segment of society, particularly the places of worship. Covid 19 pandemic negates the biblical injunction that promotes corporate worship (Hebrews 10:25). Thus, the words of Jesus Christ in Matthew 18:29 have been negated and abrogated. This paper examined the theological response of the Protestant chapel at the University of Ilorin to Covid 19 pandemic. Historical and phenomenological methods were adopted as related literature on Covid 19 pandemic was reviewed, and facts that emerged during the lockdown period were analyzed and discussed. The study discovered that the Covid19 pandemic was real with its corresponding adverse effects. Despite the lockdown, Chaplaincy introduced virtual fellowship through different platforms such as Text messages, Zoom, WhatsApp, and others. Also, it was discovered that, unlike human beings, God is not limited to the four corners of a Church building hence, he could be worshipped anytime and anywhere. The paper concluded that members of the Chapel of the Light in particular and Nigerian Christians in general while fellowshipping with one another, abided by the laid down protocols of Covid 19 pandemic. The paper recommends that the reality of the 'new normal' should enable the church to chart and develop new methods of worship and evangelism with the effective use of information and communication technology .